2014
DOI: 10.1080/15388220.2013.879367
|View full text |Cite
|
Sign up to set email alerts
|

“Just Being Mean to Somebody Isn’t a Police Matter”: Police Perspectives on Policing Cyberbullying

Abstract: Increasing public awareness of cyberbullying, coupled with several highly publicized youth suicides linked to electronic bullying, have led lawmakers and politicians to consider new criminal legislation specifically related to cyberbullying. However, little is known about how the police currently respond to cyberbullying, and it is not clear whether new laws are necessary. In this article, the authors draw upon in-depth interviews with Canadian street patrol officers and school resource officers to explore pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 26 publications
1
34
0
Order By: Relevance
“…This dynamic is most notable in cases where the perceived crime retains an online dimension, as in cases of cyber-bullying or revenge porn. As a transgression that many users perceive as criminal, it holds relatively little legal meaning, and police are sceptical or simply understaffed and unable to respond to such cases (Broll and Huey 2015). If cyber-bullying and revenge porn stand as prominent harms in contemporary digital media culture, they may contribute to a perceived vacuum of many institutions failing to address crime in which digital vigilantism emerges (Oomen 2004, p. 156).…”
Section: User/citizen-led Vigilantism As Critical Reinforcement Of Lamentioning
confidence: 99%
“…This dynamic is most notable in cases where the perceived crime retains an online dimension, as in cases of cyber-bullying or revenge porn. As a transgression that many users perceive as criminal, it holds relatively little legal meaning, and police are sceptical or simply understaffed and unable to respond to such cases (Broll and Huey 2015). If cyber-bullying and revenge porn stand as prominent harms in contemporary digital media culture, they may contribute to a perceived vacuum of many institutions failing to address crime in which digital vigilantism emerges (Oomen 2004, p. 156).…”
Section: User/citizen-led Vigilantism As Critical Reinforcement Of Lamentioning
confidence: 99%
“…Different intervention programs have been designed and tested to achieve these goals. With regard to cyberbullying, several interesting programs exist (Broll & Huey, ; Jacobs, Völlink, Dehue, & Lechner, ; Snakenborg, Van Acker, & Gable, ), but only a few have been empirically evaluated, and proven effective in decreasing cyberbullying and cyber victimization (Bauman & Bellmore, ). A number of these that focus on an educational context will be described below, although we do not claim this to be an exhaustive list.…”
Section: Introductionmentioning
confidence: 99%
“…However, the program also takes into account that traditional measures need to be reinforced by elements focused on cyberbullying and its associated contextual risks (Pabian & Vandebosch, ; Sticca et al, ). Features of safe Internet use also need to be included (Broll, ).…”
Section: Introductionmentioning
confidence: 99%
“…Based on a recent study of police officers’ perceptions of cyberbullying, the criminal justice system apparently will not offer much support. The study reported that police officers do not believe cyberbullying per se is a crime, but becomes a crime when an incident includes behaviors such as harassment and threats (Broll & Huey, 2015). In response to public opinion that the platforms themselves have some culpability, the companies that run the largest social media platforms of today have put mechanisms in place to better secure the safety of their users.…”
Section: New Media Platformsmentioning
confidence: 99%